Treatment of monazite by organic acids II: Rare earth dissolution and recovery - Lazo, D.; Dyer, Laurence; Alorro, Richard; Browner, Richard (Elsevier, 2018)
© 2018 Elsevier B.V. In the present study, the second stage of a sequential extraction method of rare earths from monazite is discussed. The high cost and environmental impact of the conventional extraction processes of rare earth elements (REEs) have driven the investigation of alternate treatment techniques. The first paper of this series detailed the solution conversion of rare earth phosphate in monazite to an oxalate salt. This was achieved via an oxalic acid leach that removed the phosphate ion from the matrix. To determine the ability of leaching to release REEs from this residue, various other organic acids (citric, tartaric, acetic, lactic, crotonic, formic, maleic, gluconic, levulinic, mandelic and EDTA) were tested as lixiviants. An alkaline EDTA solution, which reported the strongest ability to extract REEs, was tested further to maximise recovery. A maximum single-pass extraction of >60% of the Nd (the most valuable REE in this material) was achieved in just 5 min at pH 10 and ambient temperature. >40% extraction of Ce and La was also obtained, with minimal proportions of phosphorus and iron released into solution. Where multiple passes of both leach stages were performed, greater extraction of all REEs was achieved. It is apparent that REE dissolution in this system is limited by the degree of conversion achieved in the first stage. In an industrial context, the results achieved at a laboratory scale show the potential of this system to be developed into an alternative to conventional processing. The PLS generated contains far lower impurity levels than conventional processes and there is the potential for a degree of selectivity between REEs prior to separation. This system thus represents a possible reduction in technical complexity and energy requirement as well as both environmental and safety issues in comparison to conventional technologies. The ability to produce a REE hydroxide also allows it to replace conventional extraction while still employing the same separation technology.